An Imaginative Massage Photography Students: Reels as New Diary on Instagram - Aziz, Basyarul (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
This paper dicussses the process of cretaing video works in the context of the world of photography students of Institut Seni Indonesia Padangpanjang in the real world and the virtual world. The two worlds explain the private dan public life of photographers, which merge into the basis of the process of creating video works. The approach uses social media ethnography to look at a series of online social media activities that are related to and influenced by offline activities. Instagram is a place for photography students at Institut Seni Indonesia Padangpanjang to carry out online activities and upload the work created. Various features in Instagram are provided to accomodate photography students of Institut Seni Indonesia Padangpanjang to show the work they create through videous in the reels feature and show the meaning of themselves an their work. Analysis of the world of photography students provide 4 (four) series of processes in the creation of instagram video reels using Jean Baudrillard's views of "simulacra hyperreality", namely (1) the phase of reflecting the basic reality (simulation), (2) covering and distorting reality, (3) covering the absence of basic reality, (4) showing the dissapea